PENGARUH CAMPURAN BAHAN ADDITIVE KAPUR TOHOR (CaO) DAN FLY ASH TERHADAP STABILISASI TANAH DASAR LEMPUNG - Eri Setia Romadhon; Noviana Putri Kosasih; Muhammad Nafhan Isfahani (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2019)
Clay is a multi-component soil, the soil is shrinking or hard if it has low water content, whereas if the water content is high it will be soft or inflated, plastic and cohesive, experience a development and shrinkage event that takes place relatively quickly so it can endanger a construction. The first step is to find out what the optimum water content value is in the original clay soil in terms of the Atterberg Limits test value and the UCS (Unconfined Compressive Strength) test with different ripening periods using a mixture of fly ash and lime. Based on the results of testing and discussion that has been carried out on silt clay samples stabilized using a mixture of Cretaceous and Fly ash with different compositions, several conclusions are obtained: Properties of soil moisture content = 81.05%, Specific Gravity Original Land = 2.74, Analysis of Grain and Hydrometer Size: Clay = 52.57%, Silt = 43.26%, and Sand = 4.17%. From the results of the Atterberg test for native land, the liquid limit value was 73.17%, and the plastic limit was 42.08% with a plasticity index of 31.09%. So based on the classification of USCS the research soil belongs to the MH-OH symbol group, has moderate to high plasticity and contains mica or diatome elastic silts